Strategi Model Bisnis Startup Pupuk Berbasis Inovasi Limbah Ternak dan Cangkang Telur di Kabupaten Jember - Anarofida Anarofida; Ratih Apri Utami; Meihilda Dona Pratiwi; Rizky Bangkit Pamungkas; Sapna Dwi Elisa; Ubaidillah Ubaidillah (JSEP (Journal of Social and Agricultural Economics), 2022)
The scarcity of fertilizers provides an opportunity for startup businesses to provide alternative organic fertilizers. PTC Organic is one of the pioneering business startups in producing alternative fertilizers that utilize livestock waste as the main ingredient in the form of egg shells, chicken bones, and beef bones that involve a series of processes so that they become available nutrients for plants. The research method used is descriptive-analytic using the Bussiness Model Canvas (BMC) method and SWOT analysis. The objectives of this research are 1) to map out the current PTC Organic business model using BMC, (2) to develop alternative business development strategies using the SWOT method. Internal and external factors include seven aspects of internal factors (Product, Price, Promotion, Business Location, Process, People, and Physical Evidence) and four aspects of external factors (Industrial Competitors, Suppliers, New Entrants, and Buyers). The results obtained are the position of Organic PTC is very profitable, namely in Quadrant I (0.3, 0.22). So anaggressive strategy in creating innovation and product development is necessary for the sustainability of PTC Organic's business.